X-ray Binary Transients in the Magellanic Clouds and the Milky Way: Workshop 6. Issue Volume 14:Issue S339(2018) (November 2017) - Charles, P.; Anderson, G.; Coppejans, D.; Motsoaledi, M.
Abstract: The X-ray sky is dominated by luminous galactic sources, variable on time-scales from milliseconds to years. Their eruptive behaviour is now under continuous monitoring by MAXI, Swift, INTEGRAL and other high-energy missions, and representing a superb exemplar of time-domain astronomy. Understanding the astrophysics of such variability requires multi-wavelength follow-up studies from a suite of ground- and space-based facilities. As SALT is a 100% Q-scheduled telescope, one of its key scientific capabilities is related to Target-of-Opportunity (ToO) programmes, and there has been a dedicated SALT Large Programme on Transients in place since 2016, a significant fraction of which has been devoted to the follow-up of X-ray binary transients. This Workshop addressed questions of how such programmes should evolve once the era of MeerKAT and MeerLICHT begins in ∼2018-9 (as well as other huge surveys at optical wavelengths), identifying the range of facilities that would be needed, and the key science topics. There is a clear and growing need for responses to transients to be faster (within minutes if possible), and to be multi-wavelength (particularly in radio and X-ray). Furthermore, extended ongoing coverage of such events (days to weeks for the next 'V404 Cyg'-type outburst) will be needed for maximum astrophysical return. That would require careful management and coordination of a wide range of ground- and space-based facilities, and optimising coverage against logistical constraints that are often conflicting.